ISOLATION AND ACTIVITY ANTIBACTERIAL OF ISOLATES ENDOPHYTE FUNGI OF JATROPH MULTIFIDA L. STEM - Herwin, Herwin; Kosman, Rachmat; Wahyuni, Sri (Fakultas Farmasi, Universitas Muslim Indonesia, 2021)
Endophytic fungi that live on plant tissue has the potential to produce secondary metabolites, same as its host. This study aims to isolation endophyte fungi and antibacterial activity of isolate endophyte fungi of Jatropha multifida L. stem to Escheriacia coli and Staphylococcus aureus bacteria. The preliminary research was performed by isolation endophyte fungi of Jatropha multifida L. stem use PDAC medium and the result of isolation endophyte fungi Jatropha multifida L. stem obtained 6 isolates. Isolates endophyte fungi done examination morphology by microskopic method obtained that islolates have different carasteristic. Based on examination of antibacterial activity by agar diffusion method showed that isolates endophyte fungi that potential as antibacterial is isolate IFJT1 code where isolate IFJT1 code active to Escheriacia coli bacteria obtained inhibitory zone diameter of 17,7 mm and to Staphylococcus aureus bacteria.obtained inhibitory zone diameter of 16,7 mm